Plant–Soil–Climate Interaction in Observed and Simulated Tree-Radial Growth Dynamics of Downy Birch in Permafrost - Marina V. Fonti; Marina V. Fonti; Ivan I. Tychkov; Ivan I. Tychkov; Vladimir V. Shishov; Vladimir V. Shishov; Vladimir V. Shishov; Alexander V. Shashkin; Anatoly S. Prokushkin; Anatoly S. Prokushkin (Frontiers in Plant Science, 2022)
Climate change projections forecast most significant impacts on high-latitude forest ecosystems. Particularly, climate warming in boreal regions should increase fire severity and shorten its return interval. These processes can change the dynamics of boreal forests as younger stands become more dominating with a shift from gymnosperm to angiosperm. However, despite angiosperm’s phenological and physiological traits have a high potential for ecophysiological and dendroclimatological studies in Siberia, they have been rarely investigated due to their short-term lifespan in comparison with gymnosperm. Modeling tree growth is a common way to understand tree growth responses to environmental changes since it allows using available experiment or field data to interpret observed climate–growth relationships based on the biological principles. In our study, we applied the process-based Vaganov–Shashkin (VS) model of tree-ring growth via a parameterization approach VS-oscilloscope for the first time to an angiosperm tree species (Betula pubescens Ehrh.) from continuous permafrost terrain to understand its tree-radial growth dynamic. The parameterization of the VS model provided highly significant positive correlations (p < 0.05) between the simulated growth curve and initial tree-ring chronologies for the period 1971–2011 and displayed the average duration of the growing season and intra-seasonal key limiting factors for xylem formation. Modeled result can be valid at the regional scale for remote birch stands, whereas, justification of the local non-climatic input data of the model provided precise site-specific tree growth dynamic and their substantiated responses to driving factors.